(untitled) (Journal of Engineering, 2013)
Exposure of reinforced concrete buildings to an accidental fire may result in cracking and loss in the bearing capacity of their major components, columns, beams, and slabs. It is a challenge for structural engineers to develop efficient retrofitting techniques that enable RC slabs to restore their structural integrity, after being exposed to intense fires for a long period of time. Experimental investigation was carried out on twenty one slab specimens made of self compacting concrete, eighteen of them are retrofitted with CFRP sheets after burning and loading till failure while three of them (which represent control specimens) are retrofitted with CFRP sheet after loading till failure without burning. All slabs had been tested in a simply supported span and subjected to two-point loading. The main variables were the effect of different temperature levels (300ºC, 500ºC and 700ºC),different concrete compressive strength (20MPa, 30MPa and 40MPa) and cooling rate (gradually and sudden cooling conditions) on the behavior of retrofitted one way slabs .The structural response of each slab specimen was investigated in terms of load-deflection behavior, ultimate load carrying capacity and mode of failure. The experimental results, generally, indicate that slabs retrofitted using CFRP sheets restored flexural strength values nearly equal to or lower than those of the reference slabs, the retrofitted slabs exhibited larger deflection than the control slabs at ultimate loads. Retrofitted control slabs after loading regained about 93.95% to 97.92% of their original load capacity (before retrofitting) while the other slabs regained from 42.% to 84% of the load capacity of the original control specimens. Most of the tested slabs failed by concrete crushing at mid span and partial debonding of certain retrofitting systems was also observed for a few cases